2018
DOI: 10.24321/2454.8642.201804
|View full text |Cite
|
Sign up to set email alerts
|

Role of Iron Deficiency in Chronic Diffuse Hair Loss

Abstract: There are conflicting reports of association between iron deficiency and hair loss in the literature. So we conducted this study to evaluate the role of iron deficiency in chronic diffuse hair loss in women of reproductive age group. Serum ferritin, a marker of iron deficiency, was recorded in 150 consecutive patients of chronic diffuse hair loss (FPHL n=69, CTE n=81) and in healthy controls (n=100). The mean serum ferritin (SF) recorded was 9.87, 10.80, 10.30 and 11.20 ng/mL for FPHL, CTE, total patients (FPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a similar vein, Shrivastava (14) discovered a substantial difference in the incidence of aberrant thyroid function between patients and controls (TSH). When compared to the prevalence in the control group (4%), their study found a significant incidence of impaired thyroid function (11.50%).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a similar vein, Shrivastava (14) discovered a substantial difference in the incidence of aberrant thyroid function between patients and controls (TSH). When compared to the prevalence in the control group (4%), their study found a significant incidence of impaired thyroid function (11.50%).…”
Section: Discussionmentioning
confidence: 90%
“…Circulating T4 mostly affects peripheral organs, such as human hair follicles, after deionizing to T3 (10) . Additionally, T3 and T4 both greatly promote the production of intrafollicular melanin (14) . Important hair follicle processes include anagen phase prolongation, activation of the hair matrix, keratinocyte proliferation and pigmentation, and modulation of intracellular keratin expression are all directly influenced by T3 and T4 (15) .…”
Section: Introductionmentioning
confidence: 99%